Optimization of ultrasound-assisted extraction of procyanidins from perilla seed hull and their antioxidant activities in vitro - LI,Hui-Zhen (2019)
Abstract Ultrasound-assisted extraction (UAE) was used to extract procyanidins (PC) from the perilla seed hull. Four independent variables, namely, liquid-to-solid ratio, ethanol concentration, UAE time, and UAE temperature were investigated. Response surface methodology was performed on the basis of results of single-factor tests. The optimal conditions for PC extraction were as follows: a liquid-to-solid ratio of 15:1, an ethanol concentration of 62%, a UAE time of 29 min, and a UAE temperature of 53 °C. Under these conditions, the experimental yield of PC was 2.185 mg/g (n = 3), which is correlated with the predicted value of 2.2 mg/g. The extracted and purified PC showed excellent antioxidant activity against 2,2-diphenyl-1-picrylhydrazyl, hydroxyl, and 2,2’-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) radicals in vitro.